Analysis of circRNA regulatory network in myocardial tissue of type 1 diabetic mice - Li, Jianjun; Li, Xiaoxiao; Qiao, Xiaoming (Cellular and Molecular Biology, 2021)
Type 1 diabetes mellitus, also called insulin-dependent diabetes is associated with elevated blood glucose concentration arising from the inability of the pancreas to produce insulin. Diabetic cardiomyopathy is a major cause of death in diabetic patients. CircRNAs have been reported to participate in various human diseases, including diabetic cardiomyopathy. In this study, the regulation network of circRNA in type 1 diabetes mellitus was investigated. Streptozotocin treatment was implemented to induce type 1 diabetes mellitus in the mouse model, and echocardiography was implemented to detect the heart function of the type 1 diabetes mellitus mouse. Also, the qRT-PCR assay was used to identify the circRNA expression in type 1 diabetes mellitus mouse myocardial tissue. Findings showed that heart function of type 1 diabetes mellitus mouse was significantly damaged than control group mouse and cardiac hypertrophy in type 1 diabetes mellitus mouse, circRNAs were aberrantly regulated in type 1 diabetes mellitus mouse myocardial tissue. The following circRNAs were mmu_circ_0001560, mmu_circ_0001800, mmu_circ_0001801, mmu_circ_0002281 and mmu_circ_0000614 were expressed low in type 1 diabetes mellitus mouse myocardial tissue. In conclusion, type 1 diabetes mellitus caused alterations in the regulation network of circRNAs.